Parametric Simulation Analysis of the Electromagnetic Force Distribution and Formability of Tube Electromagnetic Bulging Based on Auxiliary Coil - Li Qiu; Chenglin Wang; Ahmed Abu-Siada; Wang Bin; Zhang Wang; Weikang Ge; Chang Liu; Peng Chang (IEEE Access, 2020)
Tube electromagnetic bulging has been given much attention due to its superior advantages in the field of light alloy processing. However, the conventional tube electromagnetic bulging process exhibits some critical issues that restrict its wide industrial applications. This includes non-uniform axial deformation and poor forming performance such as wall thickness thinning. This article proposes a cost-effective solution for such issues through simultaneous radial and axial electromagnetic force loading using an auxiliary driving coil. In this regard, the influence of the auxiliary coil geometrical parameters on the electromagnetic force distribution and tube forming performance is investigated using electromagnetic-structure coupling model of the bulging process. The robustness of the new proposed method is validated by comparing its electromagnetic force distribution and tube forming performance with the traditional cylindrical coil method, currently used by industry practice. Numerical results show that the introduction of the auxiliary coil may effectively weaken the radial electromagnetic force at the end of the tube and solve the uneven axial deformation issue. Based on the obtained results, the maximum uniform deformation area is increased from 6.9mm to 35.1mm. The tube relative wall thinning issue is reduced and the relative wall thickness reduction of the pipe is found to be 0.01661. The axial electromagnetic force can be further improved by adjusting the geometrical parameters of the coil and the proposed electromagnetic bulging can effectively increase the uniform deformation range of the tube.